2015
DOI: 10.3390/foods4010034
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Listeria monocytogenes in Mediterranean-Style Dry Fermented Sausages

Abstract: The morphological, physiological and epidemiological features of L. monocytogenes, together with the severity of human listeriosis infections, make L. monocytogenes of particular concern for manufacturers of cold-stored “ready to eat” (RTE) foods. L. monocytogenes has been isolated from a wide variety of RTE foods and is responsible for several outbreaks associated with the consumption of RTE meat, poultry, dairy, fish and vegetable products. Although L. monocytogenes is among the most frequently-detected path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 78 publications
4
58
0
Order By: Relevance
“…Once introduced into the plants, L. monocytogenes can persist over time in the processing environment. Not surprisingly, L. monocytogenes is among the most frequently detected pathogens in meat products, and several studies have documented the incidence of the pathogen reaching prevalence levels of up to 40%–45% [1]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Once introduced into the plants, L. monocytogenes can persist over time in the processing environment. Not surprisingly, L. monocytogenes is among the most frequently detected pathogens in meat products, and several studies have documented the incidence of the pathogen reaching prevalence levels of up to 40%–45% [1]. …”
Section: Discussionmentioning
confidence: 99%
“…According to a recent review by Meloni [1], the level of contamination by L. monocytogenes in food and non-food contact surfaces in meat processing environment ranges between 17%–50% and 11%–25%, respectively. The present study showed that 22.72% of work surfaces tested positive for L. monocytogenes .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of post‐treatment contamination is much more likely to occur during the production of typical and traditional dry fermented sausages; the association of artisan practices, and the poor hygienic conditions that could be present in processing plants often close to the farm, may result in contamination and survival of foodborne pathogens (Meloni, ; Panagou, Nychas, & Sofos, ).…”
Section: Resultsmentioning
confidence: 99%